2014
DOI: 10.1097/olq.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, Sexually Transmitted Infections, and Viral Hepatitis by Urbanicity, Among Men Who Have Sex With Men, Injection Drug Users, and Heterosexuals in the United States

Abstract: Infections with higher prevalence in urban areas merit a geographically focused approach to screening and prevention programs, whereas those with uniform prevalence across levels of urbanicity would benefit from a generalized prevention approach. These nationally representative, population-based data allow for more effective planning for prevention programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 7 publications
2
18
0
1
Order By: Relevance
“…Furthermore, the study was limited to a single-site, and results may not be generalizable to other populations. However, the temporal trends observed in this report are compatible with previous serological studies [13, 16, 18, 3638]. …”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, the study was limited to a single-site, and results may not be generalizable to other populations. However, the temporal trends observed in this report are compatible with previous serological studies [13, 16, 18, 3638]. …”
Section: Discussionsupporting
confidence: 93%
“…This finding may be due to a generational change in attitudes toward homosexuality, as has been found in population-based data [21], and resultant decreases in bisexual behavior among younger generations of MSM for whom homosexuality is more widely accepted. Moreover, MSM in smaller metropolitan and nonmetropolitan areas and those in the South and Midwest were more likely to link to heterosexual women, which may suggest that they are more likely to engage in bisexual behavior than MSM in large metropolitan areas and MSM in the Northeast and West, respectively; a previous study found that MSM in smaller metropolitan and nonmetropolitan areas were far less likely to identify as gay [22]. …”
Section: Discussionmentioning
confidence: 99%
“…17 Recent estimates among all sexually active men who have sex with men living in a large metropolitan area indicate that the seroprevalence of HSV-2 infection is 24.5%. 25 Homeless and unstably housed women are not currently included as a high-risk population in national guidelines, yet the seroprevalence of HSV-2 infection is more than three times higher. Data presented in this study indicate that revising current guidelines to include women who experience housing instability in screening strategies would target a population with an especially high seroprevalence of infections.…”
Section: Discussionmentioning
confidence: 99%